Seasonal influence on cone penetration test: An unsaturated soil site example - Giacheti, Heraldo Luiz [UNESP] (2019)
Interpretation of electric cone penetration test (CPT) based pore water pressure measurement (CPTu) is well established for soils with behavior that follows classical soil mechanics. The literature on the interpretation of these tests performed on unsaturated tropical soils is limited, and little is known about the influence of soil suction on in situ test data. In this context, the CPT data are presented and discussed to illustrate the seasonal variability in an unsaturated tropical soil site. The test data show that soil suction significantly influenced CPT data up to a depth of 4 mat the study site. It shows the importance of considering seasonal variability in unsaturated soil sites caused by soil suction, which was related to water content through a soil-water retention curve (SWRC). It is also important to consider this aspect in the interpretation of CPT data from these soils. (C) 2019 Institute of Rock and Soil Mechanics, Chinese Academy of Sciences. Production and hosting by Elsevier B.V.